Analisis Hubungan Digitalisasi Marketing Dengan Profitabilas Usaha: Studi Pada UMKM Pasca Pandemi Covid-19 - Kamaruddin; Usman Usman (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2024)
This study aims to analyze the relationship between digital marketing and business profitability in UMKM in Sumbawa Regency after the Covid-19 pandemic. This research was conducted on UMKM in Sumbawa Regency after the Covid-19 pandemic. This research is an associative research to examine the relationship between two or more variables. The variables in this study are digital marketing as the independent variable (X), and business profitability as the dependent variable (Y). The population of this research is all UMKM in Sumbawa Regency in 2022, totaling 1,792 units, while the determination of the sample was carried out using a purposive sampling technique with the criteria of UMKM that have used digital marketing as a marketing medium, totaling 158 units. Data analysis was performed using simple linear regression analysis techniques, partial hypothesis testing (t test), and coefficient of determination (R2) test with the help of SPSS 16.0. The results of this study indicate that digital marketing has a positive and significant effect on the profitability of UMKM businesses in Sumbawa Regency. Digital marketing is the right marketing strategy to reach a wider consumer market so that it can increase profitability or profits for the company.